Preoperative upper limb lymphatic function in breast cancer surgery - de Rezende, Laura Ferreira [UNESP]; Pedras, Felipe Vilela; Ramos, Celso Dario; Gurgel, Maria Salete Costa (Elsevier, 2011)
Objective: To describe the preoperative upper limb lymphoscintigraphic pattern in women with breast cancer. Methods: Thirty-seven patients undergoing lymphoscintigraphy within 30 days of surgery were investigated. Lymphoscintigraphic studies of 37 upper limbs ipsilateral to surgery and 32 contralateral upper limbs were performed. The examination protocol consisted in obtaining static images of the upper limb in semi-flexion after 10 minutes, and 1 and 2 hours after subcutaneous injection of 1 mCi (37 MBq) of Tc-99m-dextran in the dorsum of the hand. The velocity of axillary lymph node visualization (I, visible at 10 minutes; II, 1 hour; III, 2 hours; and IV, invisible) and degree (intensity) of nodal uptake (a, marked; b, moderate; c,mild; and d, absent) were analyzed. Results: Optimal lymphatic functional pattern (Ia) was observed in four (11%) patients, in the ipsilateral upper limb, and six (19%), in the contralateral upper limb. Worse condition was observed in three (8%) patients (IVd) in the ipsilateral upper limb and two (6%) patients in the contralateral upper limb. The remaining patients showed intermediate states of velocity and uptake intensity. Conclusion: This study found relevant changes in preoperative lymphoscintigraphy, demonstrating preexisting functional differences in the lymphatic system. © 2011 Elsevier Editora Ltda.
Keywords: Breast neoplasm; Lymph node excision; Lymphangiogenesis; Lymphatic system; Lymphedema; Radionuclide imaging